Interactive games for grade-9 chemistry topics and its effect on the summative assessment scores in chemistry of grade-9 students - Singbenco, Emily Dueñas (University of the Philippines Visayas, 2015)
The study was conducted in order to develop Chemistry Interactive Games that will serve as formative assessments to Grade-9 science students for the second quarter. The main objective was to investigate if the developed interactive games will increase student's summative assessment results. The Chemistry Interactive Games were based on two units (Chemical Bonding and The Variety of Carbon Compounds) depicted in the curriculum guide issued by DepEd for Grade 9 Science. The Chemistry Interactive Games were packaged in a CD that comes in two versions, one for teacher-use and the other for students. Both students and experts evaluated the interactive games and found the interactive games, in general, as proficient in different aspects such as content, grammar and information technology. There was also a significant increase (p=0.000) in mastery test scores of students who played the interactive games. All the nine interactive games were found to have an effect in the formative assessment scores of students. Of the three moderating variables identified in the study, sex and ability (OLST) test scores were found to have an influence in the summative assessment scores of students who played the interactive games. Age, on the other hand, is not a factor to consider in giving the developed interactive games as formative assessment because it does not influence the summative assessment scores of students. Some aspects of the interactive games need to be improved. It is recommended that interactive games should be tried also in other grade levels. If possible, these games should be converted to application to be installed in gadgets for wider use in order to develop students' love for Chemsitry.